Reactivations after 5-methoxy-N,N-dimethyltryptamine use in naturalistic settings: An initial exploratory analysis of the phenomenon’s predictors and its emotional valence - Ortiz Bernal, Ana María; Raison, Charles L.; Lancelotta, Rafael L.; Davis, Alan K. (Frontiers in Psychiatry, 2022)
Background: The psychedelic 5-MeO-DMT has shown clinical potential due to its short duration and ability to induce mystical experiences. However, a phenomenon known as “reactivations” (similar to “flashbacks”) is a poorly understood and frequently reported phenomenon which appears associated with 5-MeO-DMT use and warranted further investigation. Aims: This study examined whether differences in age, gender, education, lifetime use, use location, and preparation strategies predict reactivations (primary outcome). Additionally, we explored how reactivations were perceived by survey respondents and whether demographic data predicted emotional valence (secondary outcome) of reported reactivations. Methods: This study used secondary quantitative data from a survey assessing epidemiological and behavioral associations of 5-MeO-DMT use in non-clinical settings (N=513). Descriptive statistics, chi-square tests, t-tests, and logistic regressions were utilized to explore aims. Results: Being female, older at the time of first 5-MeO-DMT dose, having higher educational attainment, and dosing in a structured group setting were associated with increased odds of reporting a reactivation event. Higher mystical experience scores, greater personal well-being and having had a non-dual awareness experience that was not substance-induced were associated with higher likelihood of reporting a neutral or positive emotional valence of a reactivation event. Conclusions: These findings suggest that reactivation phenomena, in this particular sample may most often represent a neutral or positive byproduct of the acute 5-MeO-DMT experience. More information is needed to best identify individuals most likely to experience a reactivation as a negative event to prevent such potential challenging outcomes.